2017
DOI: 10.3390/su9020195
|View full text |Cite
|
Sign up to set email alerts
|

Urban Growth and Flood Disasters in the Coastal River Basin of South-Central Chile (1943–2011)

Abstract: Abstract:Urban flooding is an increasing problem in developing countries, thus understanding flood dynamics is necessary to establish guidelines on urban development and flood management. This paper studied the lower reaches of the Andalien River basin, situated on the coast of the Greater Concepcion Metropolitan Area (CMA), the second most urbanized area in Chile. This basin experienced a record 21 flood events in the last 50 years. Patterns in the evolution of urban growth were evaluated using a historical a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 63 publications
2
41
0
1
Order By: Relevance
“…Historical analysis of urban development is key for enhanced understanding of flood risk evolution (Cortès et al, ; Di Baldassarre et al, ; Di Baldassarre et al, ). Our results evidenced a lack of appropriate territorial planning and flood risk management that allowed the city to grow over flood prone areas including wetlands and paleochannels in agreement with findings by Rojas, Mardones, Rojas, Martínez, and Flores (); Rojas, Munizaga, Rojas, Martínez, and Pino (). Wetlands usually act as buffer zones mitigating the effects of floods and paleochannels serve as river corridors that attenuate the magnitude of extreme floods evacuating excess runoff and should therefore be protected (Spaliviero, ) and directly used for territorial planning.…”
Section: Discussionsupporting
confidence: 90%
“…Historical analysis of urban development is key for enhanced understanding of flood risk evolution (Cortès et al, ; Di Baldassarre et al, ; Di Baldassarre et al, ). Our results evidenced a lack of appropriate territorial planning and flood risk management that allowed the city to grow over flood prone areas including wetlands and paleochannels in agreement with findings by Rojas, Mardones, Rojas, Martínez, and Flores (); Rojas, Munizaga, Rojas, Martínez, and Pino (). Wetlands usually act as buffer zones mitigating the effects of floods and paleochannels serve as river corridors that attenuate the magnitude of extreme floods evacuating excess runoff and should therefore be protected (Spaliviero, ) and directly used for territorial planning.…”
Section: Discussionsupporting
confidence: 90%
“…In general, it was observed that the regulating and cultural ecosystem services obtained a high valuation in terms of frequency of provision despite morphological, social, and environmental changes from the last earthquake. In fact, in the regulating services, the high recurrence of natural (tsunamis, floods) and anthropogenic disasters (fires) that affect the Chilean Mediterranean region [31,37,51] may have positively influenced the utilitarian valuation of the wetland by the population, as it forms part of the inhabitants' collective memory. This is not novel, and is consistent with Barbosa and Villagra [52] as wetlands are essential to mitigate the effects of such catastrophes, and are socially valued as spaces of recovery after earthquakes, especially if they provide biophysical attributes such as water [53].…”
Section: Discussionmentioning
confidence: 99%
“…It is a commercial free software, and many studies have applied it for various purposes, not only limited to flood modeling but including sediment transport simulation and dam break, etc. (e.g., [55][56][57]). The newer version of HEC-RAS even extends its capabilities to two-dimensional inundation modeling [58].…”
Section: Floodmentioning
confidence: 99%